# Solve for y (6(y+2))/3=4y-3 6(y+2)3=4y-3
Simplify 6(y+2)3.
Cancel the common factor of 6 and 3.
Factor 3 out of 6(y+2).
3(2(y+2))3=4y-3
Cancel the common factors.
Factor 3 out of 3.
3(2(y+2))3(1)=4y-3
Cancel the common factor.
3(2(y+2))3⋅1=4y-3
Rewrite the expression.
2(y+2)1=4y-3
Divide 2(y+2) by 1.
2(y+2)=4y-3
2(y+2)=4y-3
2(y+2)=4y-3
Apply the distributive property.
2y+2⋅2=4y-3
Multiply 2 by 2.
2y+4=4y-3
2y+4=4y-3
Move all terms containing y to the left side of the equation.
Subtract 4y from both sides of the equation.
2y+4-4y=-3
Subtract 4y from 2y.
-2y+4=-3
-2y+4=-3
Move all terms not containing y to the right side of the equation.
Subtract 4 from both sides of the equation.
-2y=-3-4
Subtract 4 from -3.
-2y=-7
-2y=-7
Divide each term by -2 and simplify.
Divide each term in -2y=-7 by -2.
-2y-2=-7-2
Cancel the common factor of -2.
Cancel the common factor.
-2y-2=-7-2
Divide y by 1.
y=-7-2
y=-7-2
Dividing two negative values results in a positive value.
y=72
y=72
The result can be shown in multiple forms.
Exact Form:
y=72
Decimal Form:
y=3.5
Mixed Number Form:
y=312
Solve for y (6(y+2))/3=4y-3

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top